(E)-4-(Benzyloxy)Benzaldehyde Thiosemicarbazone - Tarafder, Md. Tofazzal Hossain; Islam, M. A. A. A. A.; Crouse, Karen Anne; Chantrapromma, Suchada; Fun, Hoong Kun (International Union of Crystallography, 2008)
In the title compound, C15H15N3OS, the thiosemicarbazone group adopts an E configuration with respect to the C N bond. The benzaldehyde thiosemicarbazone fragment is almost planar [maximum deviation = 0.012 (1) A ° ], while the dihedral angle between the benzyloxy and phenyl rings is 72.48 (5). In the crystal structure, molecules are interconnected by N—H N and N—H S hydrogen bonds, forming a two-dimensional network parallel to the bc plane and are further stacked along the a axis by – interactions [centroid–centroid separation 3.9043 (7) A ° ]. The crystal structure is also stabilized by C—H interactions